“If I'm better than average, then I'm ok?”: Comparative information influences beliefs about risk and benefits - Fagerlin, Angela (2007)
OBJECTIVE: To test whether providing comparative risk information changes risk perceptions. METHODS: 249 female visitors to a hospital cafeteria were randomized to one of two conditions which differed in whether their hypothetical breast cancer risks was lower or higher than the average woman's. Participants read a scenario describing a breast cancer prevention pill and indicated their: 1) likelihood of taking the pill, and 2) perception of whether the pill provides breast cancer risk reduction. RESULTS: Compared to “below average” women, women told that their hypothetical risk of breast cancer was above average were more likely to endorse taking the pill (2.79 vs. 2.23, F = 4.95, p=0.002) and more likely to believe that the pill provided a significant risk reduction in breast cancer (3.15 vs. 2.73, F = 4.32, p=0.005), even though the risks were equivalent. CONCLUSIONS: Providing people with comparative risk information changes their risk perceptions. People who have above average risk may feel compelled to take a treatment because they are at above average risk and therefore may not thoroughly consider the trade-offs in the risks and benefits of treatment. PRACTICE IMPLICATIONS: Physicians and decision aid developers must reconsider the practice of communicating “average risk” information to patients.